The Argumentation of Narrators of Hadith Based on those who had Companionship and Committed Apostasy in Sunnah Collections - Alfaqieh , Shefa Ali (Dirasat: Shari’a and Law Sciences, 2020)
This study looks at Hadith scholars’ approval of hadiths narrated by certain companions of Prophet Muhammad (peace and blessings of Allah be upon him) who later apostatized from Islam. The study identified some of these narrator companions, stated their narrations in Sunnah collection books, and discussed the most important issues and suspicions raised about them. The study has concluded that some proven companions of the Prophet (peace and blessings of Allah be upon him) did leave Islam and most of them were late to embrace it. It also shows that most of these companions did not engage in Hadith narration greatly. The researcher only mentions four reverted Hadith narrators, namely Abdullah ibn Abi Sarh, who narrated a single hadith but was never listed in any of the six Hadith collections; and Ashath bin Qais, who has narrated a single hadith, which was narrated by another companion, listed in the two Sahihs (Bukhari and Muslim) and the four books. He had also narrated additional three hadiths listed in the four books. The first is Amr ibn Mu’adi Kerb who narrated one hadith with a weak attribution ; and Qara ibn Habira who also narrated one hadith with a weak attribution.